Diagnostico agro socioeconómico de huertos orgánicos para la seguridad alimentaria en el sitio la Yadira - Saavedra Castillo, Edgar Francisco (2010)
During the months of July to October, 2009, it is realized the work of investigation in the place of La Yadira of the urban parish Ochoa León of the Pasaje canton. In SERPAJ Organization . For which the following objectives considered: To establish I diagnose socioeconomic land of organic orchards for the nourishing security; To develop abilities and to apply strategies for the organic culture of orchard, sustainable car for the product consumption in the feeding in the community. Firstly one proceeded to the evaluation depending on the line base established to the beginning and at the end of the dissertation, on the percentage of participants who answered the orchard in his hearths and of the measurement of the grade of knowledge on the installation, handling harvests and pos crop of the orchard. Finishing the field work 57 % the families of the community, they have the safety that the application of a good organic credit we are going to improve the particles and have more retention of moisture and improve the activity microbial of the soils, as clear Suquilanda (1986). Persons of the community of the Place La Yadira prefer the vegetables cooked in 100 % and hangovers in 57 %, with regard to the experience in cultures of vegetables 50 % if they have experience and 43 % does not have it. For the crop I am executed a field day that it allowed the achievement of demonstrations of the making of plates of salt and of sweet with the vegetables harvested in the orchard and was covered evaluating the orchards established in the courts of the hearths of the participants of the process.